Ultrasound Evaluation of the Cervix to Predict Failed Labor Induction - Christian Eric Sevrin; Letícia Matheuz Martorelli; Eduardo Augusto Brosco Famá; César Eduardo Fernandes; Mauro Sancovski; Emerson Oliveira (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2019)
Abstract Objective Labor induction does not always result in vaginal delivery, and can expose both the mother and the fetus to the risks inherent to the induction procedure or a possible cesarean section. Transvaginal sonography (TVS) of the cervix is a useful tool to predict prematurity; in the present study, this tool was used to evaluate postterm induction. Methods We evaluated the ultrasound characteristics of the cervix (cervical length, cervical funneling, internal os dilation, the presence or absence of the cervical gland area [CGA], and the morphological changes of the cervix as a result of applying fundal pressure) before the onset of labor induction among women with postterm pregnancy to identify the possible predictors of failed labor induction. The Bishop score (BS) was used for comparison purposes. Three groups were evaluated: successful versus unsuccessful induction; vaginal delivery versus cesarean delivery (excluding cases of acute fetal distress [AFD]); and vaginal delivery versus cesarean delivery (including cases of AFD). A fourth group including only the primiparous women from the three previous groups was also evaluated. Results Based on the studied characteristics and combinations of variables, a cervical length ≥ 3.0 cm and a BS ≤ 2 were the best predictors of induction failure. Conclusion Although TVS is useful for screening for induction failure, this tool should not be used as an indication for cesarean section.